Insecticidal Effects of Hemocoelic Delivery of Bacillus thuringiensis Cry Toxins in Achaea janata Larvae - Ningshen, Thuirei J.; Chauhan, Vinod K.; Dhania, Narender K.; Dutta-Gupta, Aparna (Frontiers in Physiology, 2017)
Insecticidal effects of Bacillus thuringiensis Cry toxins in hemocoel of larvae have not been properly evaluated. In the present study, hemocoelic injection of four representative Cry toxins i.e., Cry1Aa, Cry1Ab, Cry1Ac and DOR5 to an economically important lepidopteran insect pest Achaea janata, induced larval mortality, reduced larval growth rate and gave rise to smaller pupae, all in a dose-dependent manner. We observed extensive degeneration as well as the disintegration of larval tissues, most notably, fat body and the possible involvement of lysosomal enzymes in tissue histolysis. The resultant “hypoproteinemia” and most relevantly, the drastic reduction of 80-85 kDa hexamerin proteins levels of hemolymph could be attributed to the pathological state of the fat body induced by Cry toxin injection. Formation of non-viable larval-pupal intermediates and emergence of defective adults also indicate toxicity effects of Cry toxins during metamorphosis. Thus, findings from our study suggest Cry toxins in larval hemocoel are also toxic to A. janata larval survival and subsequent development.